Organization and activity of university clinics: past and present - Vozniuk, Vira; Krasiuk, Serhii (The Ukrainian Scientific Medical Youth Journal)
this article reveals certain aspects of the history of the establishment of university clinics in Ukraine, in particular, provides information about the existence of such health care institutions as early as the end of the 19th century. at the Imperial Universities – Kharkiv, Novorossiysk and St. Volodymyr. This form of existence of medical and diagnostic institutions with the possibility of improving the practical skills of students and carrying out research activities of scientists - teachers of higher education institutions contributed to the training of highly qualified specialists and the development of science in general. The specified system of organizing the educational process corresponded to the principle of dual education, which provides for the combination of educational and research activities. Started back in 1804, it is still actively promoted by the leading national higher education institutions. It was found that the first university clinics were created at the medical departments of the university and were highly specialized – surgical, therapeutic, obstetric. According to the structural organization, they were subordinated to educational institutions. In the 1950s, by decision of the USSR government, city hospitals were created on the basis of such clinics. The problem of modernization of the health care system, which arose after the collapse of the USSR and the transition of Ukraine to a new economic system of the market economy, led to the search for an optimal model of the organization of clinical bases of medical institutions of higher education. In the 80s of the XX century. the initiated reform of higher medical education has been improved by improving the quality of professional training of future doctors, in accordance with world and pan-European standards, taking into account national priorities and features of the health care system. The Ministry of Education and Culture of Ukraine has developed uniform approaches to educational and qualification characteristics and educational and professional programs at the stages of undergraduate and postgraduate training of specialists. Programs of clinical disciplines provide for early contact with the patient, responsibility for clinical observations, and practical work experience. The reform of higher medical education is aimed at a gradual transition from an information-accumulating to a competency-based model of the formation of knowledge, skills and abilities of future doctors. At the beginning of the 2000s, based on our own historical experience, and having familiarized ourselves with the practice of foreign higher educational institutions of the medical profile, it was decided to resume the activities of university clinics. Today, there are more than 10 educational-scientific-treatment complexes with an integrative and corporate model of existence. The content of the article informs about their founding periods, main tasks and areas of activity, form of existence, regulatory documents, etc.